Environmentally Friendly Wood Adhesives Based on Dextrin/Arabic Gum Blends - Huda M. J. Ali; Ahmed Q. Abdullah; Zainab J. Shanan (Iraqi Journal of Industrial Research)
Wood adhesives are widely used consisting of urea-formaldehyde resins. Most of the studies aim to find alternative natural materials to replace the carcinogenic chemical adhesives. A mixture of natural materials that are available in abundance, cheap in price and are resistant to water and heat, the failure of the interface between two solid dielectrics is a major source of insulation system failure, hence it is crucial to understand the principles regulating this breakdown occurrence. It is generally agreed that the tangential AC breakdown strength of solid-solid surfaces is primarily determined by the elastic modulus (elasticity), radial/tangential pressure, surface smoothness/roughness, and dielectric strength of the ambient environment. For this purpose, we made use of dextrin and Arabic gum. Physical parameters (Lap shear strength, pull off strength, hardness, roughness, electrical and thermal insulations) of the combination formed with varying amounts of each ingredient were investigated. The adhesive characteristics of D were enhanced by the incorporation of AG, with improved pull off adhesion and lap shear strength at increasing AG levels at 80%. D /AG 20/80 compositions had pull off adhesion values 189 times greater than pure D, and lap shear strength values 820 times higher. It is evident because of the dispersion of AG molecules in decreasing the surface roughness of D/AG films and increasing their hardness on the shore scale. There is a positive correlation between the amount of AG added and the blending matrix of D, therefore boosting A with AG increases A. The dielectric strength, and thermal insulation increases with the increase in the weight ratio of Arabic gum. The blend prepared as an adhesive for wood is a good electrical and thermal insulator at 8% AG/20% D.